Decreasing motor stereotypy with competing stimuli and tasks: Analysis of prompted engagement and response blocking. (29th April 2021) - Schmidt, Jonathan D.; Falligant, John M.; Goetzel, Amanda; Hardisty, Shelby; Hagopian, Louis P.
Abstract: Competing stimulus assessments (CSAs) are used to empirically identify stimuli associated with low levels of problem behavior. For some individuals with automatically maintained behavior, it can be difficult to identify effective competing stimuli. Recent research shows that prompting engagement and response blocking can be employed during the CSA to obtain significant reductions in problem behavior. The purpose of the present study was to replicate and extend prior research on the use of these tactics not only with competing stimuli, but also competing tasks, which require the active completion of a discrete response or response sequence. In addition, the current study validated the results of these pretreatment assessments in an extended treatment analysis, and examined the isolated and combined effects of prompting and response blocking within a component analysis. Future research directions and implications for clinical practice are discussed.